Liability Of A Doctor Who Perform A Malpractice (A Review Under Health Law) - Benny L.H Hutahaean (Institute Of computer Science (IOCS), 2022)
The problems that will be discussed by the author in the writing of this thesis are: What are the limitations that can be used to determine that a doctor has committed medical malpractice on a patient; What actions or legal remedies can a patient or his family take if he is exposed to medical malpractice; What sanctions can be imposed on doctors who commit medical malpractice as a form of responsibility of doctors to their patients. The type of research used in this paper is a normative juridical research, namely research conducted on written regulations governing health law and legal materials related to medical malpractice. In discussing medical malpractice involving two different disciplines, namely medical science and health science, this paper will use the